2015
DOI: 10.1002/cphc.201500580
|View full text |Cite
|
Sign up to set email alerts
|

Immersion Calorimetry: Molecular Packing Effects in Micropores

Abstract: Repeated and controlled immersion calorimetry experiments were performed to determine the specific surface area and pore-size distribution (PSD) of a well-characterized, microporous poly(furfuryl alcohol)-based activated carbon. The PSD derived from nitrogen gas adsorption indicated a narrow distribution centered at 0.57±0.05 nm. Immersion into liquids of increasing molecular sizes ranging from 0.33 nm (dichloromethane) to 0.70 nm (α-pinene) showed a decreasing enthalpy of immersion at a critical probe size (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 30 publications
7
26
0
Order By: Relevance
“…The PSD calculated from a QSDFT application confirmed this supposition, indicating a narrow, primary distribution of pores centred at 0.57 ± 0.05 nm, also consistent with previous studies based on repeated isotherm measurements [22] and on model-independent methods such as calorimetry and isosteric heat analyses [20,34,35].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The PSD calculated from a QSDFT application confirmed this supposition, indicating a narrow, primary distribution of pores centred at 0.57 ± 0.05 nm, also consistent with previous studies based on repeated isotherm measurements [22] and on model-independent methods such as calorimetry and isosteric heat analyses [20,34,35].…”
Section: Resultssupporting
confidence: 89%
“…derives from the proximity of the mean pore size to the adsorptive's kinetic diameter. These effects were proposed by Brunauer et al [36], supported by Rege and Yang [37], and more recently confirmed by immersion calorimetry studies of this PFA-based carbon (mean pore width = 0.57 ± 0.05 nm) into MeOH and iso-PrOH [20]. These enthalpy measurements suggested there was a negligible influence of packing effect during adsorption filling for MeOH since its kinetic diameter (0.43 nm) was considerably smaller than the mean pore size.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…activated carbons, activated carbon fibers, carbon molecular sieves, carbon xerogels/aerogels and coals) is one of the fundamental steps in understanding and improving their respective performance in technical applications including separations, sequestrations, gas storage, supercapacitors and batteries, adsorption/desorption heat pumps, catalysis, and many others [1][2][3][4][5][6][7]. Various experimental and theoretical studies conducted on this subject concluded that disordered carbonaceous materials could be described as nano-scale pores of various sizes embedded into a disordered carbon matrix [8][9][10][11][12][13][14][15][16]. For most carbonaceous materials the majority of relevant pore volume is related to micropores, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the previous studies cannot draw solid conclusions about the pore size and surface chemistry that maximize the capture of formaldehyde. It is not surprising because carbonaceous materials are both structurally and energetically heterogeneous [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The intrinsic distribution of pore sizes and diversity of various surface functional groups hamper our ability to understand microscopic details of the mechanism of dynamic formaldehyde adsorption at ~ppm concentrations.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%